Exploiting haptic facets: Users' sensemaking schemas as a path to design and personalization of experience. Issue 107 (November 2017) - Seifi, Hasti; MacLean, Karon E.
Abstract: Our poor understanding of the connection between haptic effect engineering – using controllable parameters like frequency, amplitude and rhythm – and how sensations are comprehended by end-users hinders effective design. Haptic facets (categories of attributes that characterize collection items in different ways) are a way to describe, navigate and analyze the cognitive frameworks by which users make sense of qualitative and affective characteristics of haptic sensations. Embedded in tools, they will provide designers and end-users interested in customization with a road-mapped perceptual and cognitive design space. We previously compiled five haptic facets based on how people describe vibrations: physical, sensory, emotional, metaphoric, and usage examples . Here, we report a study in which we deployed these facets to identify underlying dimensions and cross-linkages in participants' perception of a 120-item vibration library. We show that the facets are crosslinked in people's minds, and discuss three scenarios where the facet-based organizational schemes, their linkages and consequent redundancies can support design, evaluation and personalization of expressive vibrotactile effects. Finally, we report between-subject variation (individual differences) and within-subject consistency (reliability) in participants' rating and tagging patterns to inform future progress on haptic evaluation. This facet-based approach is also applicable to other kinds of haptic sensations and even other modalities, and can inform multimodal experience design through a descriptive design language shared between different modalities. Abstract : Highlights: Empirically derived semantic dimensions of four VT facets. Between-facet linkages at dimensional and tag levels, and their implications for VT design. Analysis of individual variations in rating and annotating vibrations. A two-step methodology for annotating large VT sets, and data on its validity and reliability. A publicly available dataset of 120 vibrations and their annotations and dimensions.